2018
DOI: 10.4236/ajps.2018.911165
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Varied Irrigation Scheduling with Levels and Times of Nitrogen Application on Yield and Water Use Efficiency of Aerobic Rice

Abstract: More rice needs to be produced with lesser water to feed the increasing human population. Judicious water management practices and appropriate water saving technologies in rice cultivation are in need in the coming decades. Aerobic rice is one of water saving method of rice cultivation. The field experiment was conducted during Summer season of February 2018 to May 2018 at Tamil Nadu Agricultural University, Agricultural College and Research Institute, Madurai, to find out the effect of irrigation schedules wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that compared to continuous flooding, all water-saving practices allow for sustainable rice production [127]. According to research [126][127][128][129][130], there are multiple water-saving technologies, including alternate wetting and drying (AWD), soil water potential (SWP), non-flooded mulching cultivation, aerobic rice system (ARS), efficient irrigation regime (EIR), saturated soil culture (SSC), field water level (FWL), intermittent drainage (ID), leaching and flushing methods (LFM), conventional flooding-midseason drainage-flooding irrigation (FDF), etc. The most popular water-saving technologies developed for rice production systems is the alternate wetting and drying (AWD) [121,123].…”
Section: Water-saving Irrigation Practices For Rice Productionmentioning
confidence: 99%
“…Previous studies have shown that compared to continuous flooding, all water-saving practices allow for sustainable rice production [127]. According to research [126][127][128][129][130], there are multiple water-saving technologies, including alternate wetting and drying (AWD), soil water potential (SWP), non-flooded mulching cultivation, aerobic rice system (ARS), efficient irrigation regime (EIR), saturated soil culture (SSC), field water level (FWL), intermittent drainage (ID), leaching and flushing methods (LFM), conventional flooding-midseason drainage-flooding irrigation (FDF), etc. The most popular water-saving technologies developed for rice production systems is the alternate wetting and drying (AWD) [121,123].…”
Section: Water-saving Irrigation Practices For Rice Productionmentioning
confidence: 99%